Rynek lasu – metody dochodowe określania wartości zasobów leśnych - Zając, Stanisław; Klocek, Andrzej (Leśne Prace Badawcze, 2019)
This article describes methods for estimating the value of a forest, the accurate estimation of which is crucial for purchases and sales, in credit security, in determining the shares in the division of forest real estate, as well as in determining the amount of compensation for any losses in forest property. Compensation for property losses also includes past events that occurred before the Second World War such as nationalization or leaving in the eastern territories of the Second Polish Republic (1918-1939). An equally important objective of forest valuation, which has recently gained in importance, is the inclusion of its value in the forest management balance. However, due to the lack of fully objective market prices for forest property, this work focused on the analysis of quantitative and qualitative characteristics of the forest market and the methods for calculating the income (rent) value of the forest. Included are examples of commercial transactions on the forest market in the USA, Austria and Germany.The study presents a historical outline of the forest valuation with particular emphasis on methods based on the income value, including the forest rent. Furthermore, we discuss the formula of perpetual capitalization of annuity and periodic annuity including the various net income impact variations, i.e. from below or from above.